Young environmental scientist (Y.E.S) program to enhance the environmental awareness among the Malaysian school students - Hafizan, Juahir; Azman, Azid; Mohd Khairul Amri, Kamarudin; Mohd Ekhwan, Toriman (2014)
Environmental pollution and awareness issues are recognized as one of the major components of the global environmental crisis. This study tries to design and develop the effectiveness program in order to enhance the environmental pollution and awareness among the school students in Malaysia. Young Environmental Scientist (Y.E.S) Program was designed in order to bring all the students to gain new experience about how the scientist did their research especially in identifying the environmental pollution problems. Forty (40) of the secondary school students (form four); five teachers and two researchers from the university were involved in this program. The study areas were located in Jeli District, State of Kelantan. The assessments of river water quality were chosen as a case study. The application of in-situ measurement of river water quality was designed as field sampling activities. The six selected water quality parameters; namely dissolved oxygen (DO), suspended solid (SS), turbidity (Tur), colour (Col), electrical conductivity (EC) and pH was measured using portable instruments. The results show, all the participants clearly understand the determination of surface river water quality by using the in-situ measurements technique. Finally, the YES program was successfully delivered and increase the knowledge of environmental protection and prevention among the students. This program hope can be inspired among Malaysian school students in the environmental pollution and awareness.